Diseño e implementación de un sistema de facturación para mejorar el cobro del arrendamiento de plazas y mercados utilizando la tecnología wap en el gobierno autónomo descentralizado municipal del Cantón Saquisilí Provincia de Cotopaxi - Toapanta Casa, Víctor Alfonso (2013)
The present research deals the present situation in order to collect Money to the traders from Saquisilí Canton Municipal GAD, to use public places for economic activities in different squares and markets, in which it mention the different sales that involve in the process. Also it includes the methods, types, techniques and tools that allowed to develop the research, the methods used for the implementation of the proposal were the hypothetical deductive, synthetic analytical, scientific, inductive deductive and descriptive method, the research techniques that were used are the interview and survey in order to know the real situation of the issues and determine appropriate solutions.